A governance network perspective on environmental conflicts in China: findings from the Dalian paraxylene conflict. (3rd July 2016) - Liu, Yi; Li, Yanwei; Xi, Bao; Koppenjan, Joop
ABSTRACT: Employing the Governance Network framework, this article presents an in-depth case study of the conflict that evolved from 2003 onwards over the construction and operation of a paraxylene plant in Dalian, China. The study explores the usefulness of this framework as an empirical tool to describe and make sense of policy processes and governance in multi-actor situations in China. The analysis shows the lack of anticipation and deliberation by Chinese governments, resulting in the buildup of citizens' concerns, mediated by social media beyond government control. This results in an outbreak of protest followed by uncoordinated governmental responses, with high costs for all parties. It is argued that, because of the underlying institutional causes, the challenges are even greater for Chinese governments to come to grips with the increasing need for internal coordination, deal with new social media, and balance economic and environmental values.